High energy density zinc-air microbattery utilising inorganic MCM-41 membrane - Saputra, Hens; Othman, Raihan; Ani, Mohd Hanafi; Sutjipto, Agus Geter Edy; Muhida, Riza (Maney Publishing, 2011)
An ultrathin, high energy density zinc–air cell has been developed for potential application in microsystems. The key design feature is the utilisation of an inorganic MCM-41 membrane material with three-in-one functional elements. It serves as an insulating layer between the electrodes, as ionic exchange channels and as an electrolyte reservoir matrix. As a result, a feasible, compact cell design with high discharge capability has been demonstrated. The MCM- 41 material consists of a hexagonally ordered, nanopore structure. It possesses attractive features of large surface area and pore volume, narrow pore size distribution, tunable pore size,adjustable hydrophobicity and very good thermal stability. The Zn/MCM-41/air cell measuring 1 cm2 area and ca. 300 m thick is able to deliver a maximum discharge current of 30 mA and possesses an optimum capacity of 35 mAh.